Association Between Urinary Markers of Nucleic Acid Oxidation and Mortality in Type 2 Diabetes: A population-based cohort study - Broedbaek, Kasper (American Diabetes Association, 2013)
OBJECTIVE: We recently showed that RNA oxidation, estimated by urinary excretion of 8-oxo-7,8-dihydroguanosine (8-oxoGuo), independently predicted mortality in a cohort of 1,381 treatment-naive patients with newly diagnosed type 2 diabetes. In the present investigation, we analyzed urine collected 6 years after the diagnosis to assess the association between urinary markers of nucleic acid oxidation and mortality in patients with established and treated diabetes. RESEARCH DESIGN AND METHODS: We used data from the 970 patients who attended the screening for diabetes complications 6 years after the diagnosis. Cox proportional hazards regression was used to examine the relationship between urinary markers of DNA oxidation (8-oxo-7,8-dihydro-2′-deoxyguanosine [8-oxodG] [n = 938]) and RNA oxidation (8-oxoGuo [n = 936]) and mortality. RESULTS: During a median of 9.8 years of follow-up, 654 patients died. Urinary 8-oxoGuo assessed 6 years after the diagnosis was significantly associated with mortality. The multivariate-adjusted hazard ratios for all-cause and diabetes-related mortality of patients with 8-oxoGuo levels in the highest quartile compared with those in the lowest quartile were 1.86 (95% CI 1.34–2.58) and 1.72 (1.11–2.66), respectively. Conversely, 8-oxodG was not associated with mortality. In addition, we found an association between changes in 8-oxoGuo from diagnosis to 6-year follow-up and mortality, with increased risk in patients with an increase and decreased risk in patients with a decrease in 8-oxoGuo. CONCLUSIONS: The RNA oxidation marker 8-oxoGuo is an independent predictor of mortality in patients with established and treated type 2 diabetes, and changes in 8-oxoGuo during the first 6 years after diagnosis are associated with mortality.